Origin and Roles of Alanine and Glutamine in Gluconeogenesis in the Liver, Kidneys, and Small Intestine under Physiological and Pathological Conditions - Holeček, Milan (International journal of molecular sciences, 2024)
Alanine and glutamine are the principal glucogenic amino acids. Most originate from muscles, where branched-chain amino acids (valine, leucine, and isoleucine) are nitrogen donors and, under exceptional circumstances, a source of carbons for glutamate synthesis. Glutamate is a nitrogen source for alanine synthesis from pyruvate and a substrate for glutamine synthesis by glutamine synthetase. The following differences between alanine and glutamine, which can play a role in their use in gluconeogenesis, are shown: (i) glutamine appearance in circulation is higher than that of alanine; (ii) the conversion to oxaloacetate, the starting substance for glucose synthesis, is an ATP-consuming reaction for alanine, which is energetically beneficial for glutamine; (iii) most alanine carbons, but not glutamine carbons, originate from glucose; and (iv) glutamine acts a substrate for gluconeogenesis in the liver, kidneys, and intestine, whereas alanine does so only in the liver. Alanine plays a significant role during early starvation, exposure to high-fat and high-protein diets, and diabetes. Glutamine plays a dominant role in gluconeogenesis in prolonged starvation, acidosis, liver cirrhosis, and severe illnesses like sepsis and acts as a substrate for alanine synthesis in the small intestine. Interactions among muscles and the liver, kidneys, and intestine ensuring optimal alanine and glutamine supply for gluconeogenesis are suggested.
Keywords: Liver; glukosa; alanin; játra; Intestine, Small; lidé; tenké střevo; glukoneogeneze; Glutamine; branched-chain amino acids; Gluconeogenesis; zvířata; Humans; ledviny; glucose; cirrhosis; glutamin; Kidney; diabetes; starvation; Alanine; Glucose; Animals